2021
DOI: 10.21608/ejchem.2021.81233.4024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-power pain threshold ultrasound versus extracorporeal shock wave on upper trapezius myofascial trigger points.

Abstract: The aim of the study is to investigate effect of high-power pain threshold ultrasound versus extracorporeal shock wave on myofascial trigger points. Methods: this randomized single blinded controlled trial included a sample of 60 subjects (age 20 to 26) years old with upper trapezius myofascial trigger points. Subjects randomly allocated into 3 groups; Extracorporeal shock wave (ESWT) group (n=20) which received low level energy ESWT plus neck stretching, strengthening exercise, High Power Pain threshold Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The assessed outcome variables were as follows: (1) pain reported on a VAS or Numeric Pain Rating Scale in all studies, except in four trials 19,27,28,31 (2) the PPT, which was measured in 19 trials; and (3), and functionality (18 trials). The secondary variables were the quality of life, measured with the SF-36 in three studies, 17,21,34 and the ROM, measured in five studies 18,24,31,33,34 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The assessed outcome variables were as follows: (1) pain reported on a VAS or Numeric Pain Rating Scale in all studies, except in four trials 19,27,28,31 (2) the PPT, which was measured in 19 trials; and (3), and functionality (18 trials). The secondary variables were the quality of life, measured with the SF-36 in three studies, 17,21,34 and the ROM, measured in five studies 18,24,31,33,34 …”
Section: Resultsmentioning
confidence: 99%
“…In terms of the treated area, 22 studies were carried out on patients with cervical and shoulder complaints, three studies were conducted on the leg/foot region, 25,27,28 and two trials were conducted on the lumbar spine region. 22,30 On the duration of pain, eight studies reported no data on this variable, 19,20,23,28,32,33,38 five studies reported between zero days and 3 mos of pain duration, 18,24,29,33,34 and 14 studies reported that their sample had a duration of pain longer than 3 mos.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations